2022
DOI: 10.1021/acs.analchem.2c00783
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sialic Acid Isomers from Released N-Glycans Using Ion Mobility Spectrometry

Abstract: Complex carbohydrates are ubiquitous in nature and represent one of the major classes of biopolymers. They can exhibit highly diverse structures with multiple branched sites as well as a complex regio- and stereochemistry. A common way to analytically address this complexity is liquid chromatography (LC) in combination with mass spectrometry (MS). However, MS-based detection often does not provide sufficient information to distinguish glycan isomers. Ion mobility-mass spectrometry (IM-MS)—a technique that sepa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Figure e illustrates the N -glycan structures with the top 15 relative abundances identified in both CTR and T2D human serum. Notably, elevated levels of complex-type acidic N -glycan, such as [Hex]­5­[HexNAc]­4­[NeuAc]­2, were significantly observed in T2D, which is commonly associated with cancer and characterized by terminal N -acetylglucosamine . In contrast, neutral glycans such as [Hex]­4­[HexNAc]­4­[Fuc]­1 were highly expressed in the CTR group, which displayed marked differences between the CTR and T2D groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure e illustrates the N -glycan structures with the top 15 relative abundances identified in both CTR and T2D human serum. Notably, elevated levels of complex-type acidic N -glycan, such as [Hex]­5­[HexNAc]­4­[NeuAc]­2, were significantly observed in T2D, which is commonly associated with cancer and characterized by terminal N -acetylglucosamine . In contrast, neutral glycans such as [Hex]­4­[HexNAc]­4­[Fuc]­1 were highly expressed in the CTR group, which displayed marked differences between the CTR and T2D groups.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, elevated levels of complex-type acidic N-glycan, such as [Hex]5[HexNAc]4[NeuAc]2, were significantly observed in T2D, which is commonly associated with cancer and characterized by terminal N-acetylglucosamine. 37 In contrast, neutral glycans such as [Hex]4[HexNAc]4[Fuc]1 were highly expressed in the CTR group, 38 which displayed marked differences between the CTR and T2D groups. It is noteworthy that U6N/Pv@Glc facilitated the enrichment and identification of numerous low-abundance neutral glycans (excluding the top 5) bearing multiple fucose (deoxyhexose) residues, which was attributed to the advantageous capability of amide-HILIC in effectively separating neutrally charged glycans.…”
Section: Glycoproteomic Analysis Of Human Serum In Typementioning
confidence: 99%
“…Recent advancements in ion mobility technology highlighted the potential of the method to be used in LC-based glycomics analyses. 23,[37][38][39][40][41][42] Fundamental studies recently showed that IMS can be theoretically described using a plate-height model, similarly to other separation techniques such as capillary zone electrophoresis or LC. 43,44 Dedicated bioinformatics tools for deconvolution and data treatment further strengthen the utility of ion mobility in real-world applications.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of technology, more and more detection approaches have emerged. For instance, ion mobility spectrometry (IMS) has been shown to separate and identify α2-3 and α2-6 linked Neu5Ac from released N-glycans [141]. IMS possesses an essential dimension which is able to resolve isobaric species by their gas-phase collision cross-section (CCS), however, the application of IMS is usually limited by the databases of carbohydrate CCS values [142,143].…”
Section: Othersmentioning
confidence: 99%